2016
DOI: 10.1590/s0100-204x2016000800008
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and diversity in shrub savanna using ordinary kriging

Abstract: -The objective of this work was to analyze the spatial distribution and the behavior of species richness and diversity in a shrub savanna fragment, in 2003 and 2014, using ordinary kriging, in the state of Minas Gerais, Brazil. In both evaluation years, the measurements were performed in a fragment with 236.85 hectares, in which individual trees were measured and identified across 40 plots (1,000 m 2 ). Species richness was determined by the total number of species in each plot, and diversity by the Shannon di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…As such, variations in plant distributions are not random and will demonstrate some degree of spatial dependence, and this dependence cannot be identified through classical analyses (Miller et al, 2007;Batista et al, 2016) as observed in the present study. In that sense, as described by Amaral et al (2013a), analyses that assume independence among samples, have been substituted by geostatistical analyses that provide more reliable and precise data for decisionmaking by forest administrators.…”
Section: Discussionmentioning
confidence: 58%
“…As such, variations in plant distributions are not random and will demonstrate some degree of spatial dependence, and this dependence cannot be identified through classical analyses (Miller et al, 2007;Batista et al, 2016) as observed in the present study. In that sense, as described by Amaral et al (2013a), analyses that assume independence among samples, have been substituted by geostatistical analyses that provide more reliable and precise data for decisionmaking by forest administrators.…”
Section: Discussionmentioning
confidence: 58%
“…In each plot, all living arboreal individuals with diameter at 1.30 meters above ground (DBH) ≥ 5 cm were measured. Total height of these arboreal individuals was registered using a telescopic measurement stick with five centimeters of accuracy (Batista et al, 2016;Silva Neto et al, 2017;Scolforo et al, 2008). Thus, the quantification of dead and recruited trees was performed, considering as recruit all arboreal individuals that reached the minimum diameter for inclusion in each inventoried period.…”
Section: Study Areas and Data Collectionmentioning
confidence: 99%
“…A alta riqueza provavelmente se deve ao fato das parcelas terem sido alocadas distantes entre si, sendo amostradas diferentes áreas geográficas de cerrado, o que possibilita uma maior chance de se amostrar espécies novas, quando comparado com estudos nos quais se amostra uma única localização. Como a diversidade tende a ser fortemente dependente da riqueza (BATISTA et al, 2016), também esteve dentro dos padrões para cerrado. Assim, as margens da rodovia são, de fato, áreas que merecem maior atenção conservacionista por abrigarem espécies de cerrado em matrizes agropecuárias, todavia, novos estudos devem ser realizados para verificar quanto as populações de espécies de Cerrado estão sendo afetadas nestas localidades e até que ponto estas margens de rodovias podem se auto manter ao longo dos anos.…”
Section: Comparação Com Cerrados Pouco Impactadosunclassified